Proceedings of the ACM SIGGRAPH Symposium on High Performance Graphics 2011
DOI: 10.1145/2018323.2018345
|View full text |Cite
|
Sign up to set email alerts
|

Farthest-point optimized point sets with maximized minimum distance

Abstract: δ X =0.009,δ X =0.469 input δ X =0.049,δ X =0.645 1/4 iteration δ X =0.079,δ X =0.756 1/2 iteration δ X =0.772,δ X =0.865 1 iteration δ X =0.814,δ X =0.905 2 iterations δ X =0.925,δ X =0.932 63 iterationsFigure 1: Farthest-point optimization of a random point set with 1024 points. Both the global minimum distance δX and the average minimum distanceδX increase rapidly using our optimization technique. After one iteration the point set is already well-distributed. AbstractEfficient sampling often relies on irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 22 publications
0
86
0
3
Order By: Relevance
“…To avoid the regularity artifacts, a statistical model is defined to allow solutions that are less energetically-favorable. By iteratively enlarging the minimum distance between points, Schlömer et al [22] construct irregular distributions with a significantly higher minimum distance than previous methods.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the regularity artifacts, a statistical model is defined to allow solutions that are less energetically-favorable. By iteratively enlarging the minimum distance between points, Schlömer et al [22] construct irregular distributions with a significantly higher minimum distance than previous methods.…”
Section: Related Workmentioning
confidence: 99%
“…However, Schlömer (e) CapCVT result with ρ(x) = ̺ 2 (x) and ̺(x) = ϕ(x) (λ = 30) et al [22] show that Poisson disk distributions can have radii up to 0.93 or higher. Considering also the spectrum properties, we found that our method with λ ∈ [20,100] gives a point distribution with good blue noise characteristics.…”
Section: Density Function Adaptationmentioning
confidence: 99%
“…There are many algorithms for this purpose, e.g. Balzer et al 2009;Cook 1986;de Goes et al 2012;Fattal 2011;Jiang et al 2015;McCool and Fiume 1992;Schlömer et al 2011]. In all these algorithms the production cost (time and memory) is high, which leads to the idea of tabulating the blue-noise sets for subsequent reuse, replacing on-the-fly generation of sample points by a lookup framework.…”
Section: Ccs Concepts: • Computing Methodologies → Rendering;mentioning
confidence: 99%
“…Typical optimization algorithms include Lloyd's algorithm [Lloyd 1982;McCool and Fiume 1992], a localized version of Farthest Point Optimization (FPO) [Schlömer et al 2011], and the more recent Push-Pull Optimization (PPO) . Since all the mentioned algorithms are based on a Delaunay triangulation of the point set, they can easily be combined, leading to a sequence of optimizations applied to each visited point.…”
Section: Optimizing Point Positionsmentioning
confidence: 99%
“…Direct production algorithms to generate such point sets include stratified jittering, dart throwing [Dippé and Wold 1985;Cook 1986;Mitchell 1987], and their variants. There are also iterative optimization techniques to modify a given point set, including Lloyd's relaxation algorithm [McCool and Fiume 1992] and its variants [Balzer et al 2009;Xu et al 2011;Chen et al 2012;de Goes et al 2012], other iterative methods [Schmaltz et al 2010;Fattal 2011;Schlömer et al 2011], and the recently invented target-matching algorithms [Zhou et al 2012;Öztireli and Gross 2012;Heck et al 2013]. …”
Section: Related Workmentioning
confidence: 99%